Depth of Origin of the Peak (Inner) Ring in Lunar Impact Basins - Miljković, Katarina; Lemelin, M.; Lucey, P. (American Geophysical Union, 2017)
Numerical modeling of the peak-ring basin formation showed that the peak-ring forms from the material that is part of the central uplift outwardly thrust over the inwardly collapsing transient crater rim. Simulations of the lunar basin formation showed that the peak or inner ring in peak ring or multiring basins, respectively, is composed of the overturned crust and deep-seated material, possibly from the upper mantle. Numerical impact simulations were used to trace the depth of origin of material exposed within the peak (or inner) ring. We estimate the scaling trends between basin size and the depth of origin of material exposed within the ring. We also report on the likely crust, mantle, and projectile abundances exposed within the ring. Quantifying the excavation depths during the formation of the peak or inner ring provides a step toward understanding the lunar crust and mantle stratigraphy.